The Fate of Energy Arising from Renewable Sources - Mitrovic, Jovan (European Journal of Applied Sciences, 2024)
Using the wind energy as example, this notice sheds some more light on the effects of conversion of natural energy on the Earth's climate. This energy is mostly converted into electric energy that may strongly affect the climate. Its final mode is heat that is disposed as waste in the environment.